PENAMBAHAN MULTI ASAM AMINO PADA MEDIA PEMELIHARAAN LARVA RAJUNGAN Portunus pelagicus UNTUK LAJU PERCEPATAN METAMORFOSIS STADIA ZOEA HINGGA MEGALOPA - Nurul Mutmainnah; Zulfiani; Yusdalifa Ekayanti Yunus; Faidar; Muh. Yusri Karim; Fitri Indah Yani (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
The addition of multi-amino acids to the culture media for Portunus pelagicus crab larvae accelerates the metamorphosis rate from the zoea to megalopa stages. The research aims to examine the effect of adding multiple amino acids to the rearing media and determine the best dosage on the rate of acceleration of metamorphosis (stage transfer) of P. pelagicus crab larvae from zoea to megalopa stages. Test samples are taken daily to see the development of larvae or larval stage index. The test animals used in this research were zoea-1 stage crab larvae stocked at 100 individuals/L density. The container used in this research was a black plastic basin with a water volume of 30 liters. Treatment doses of amino acids were 0, 150, 200, and 250 ppm with 3 repetitions each. The research results show that administering multi-amino acids in the rearing media can accelerate the transfer rate of crab larvae stages. The fastest rate of acceleration of metamorphosis from zoea to megalopa was produced at a treatment dose of 250 ppm for 10 days, and the longest was produced at a dose of 0 ppm for 13 days. Stage transfer between sub-zoea takes 2-3 days for metamorphosis, and zoea to megalopa takes 10-13 days.